Engineering composite materials - Harris, Bryan, 1935- (IOM, 1999)
This book should prove invaluable to undergraduates on materials engineering courses and postgraduates beginning work on composites research projects. All major types of composite are covered and practical applications in aerospace, automotive, bio-engineering, electrical engineering, marine engineering and sport are covered.
Previous edition: London : Institute of Metals, 1986.
Keywords: Composite materials.; elektronické knihy; electronic books